Diseño de estrategias de marketing relacional para empresas del sector de muebles del cantón Latacunga - Espinoza Toscano, José Miguel (2017)
This project research was done with the aim of determining relational marketing strategies which best fit for furniture customers’ loyalty in Latacunga Canton. To design this strategy situational diagnosis was made, which it allowed us to know threats (increase in inflammation) growing competition, new incomes, etc.) and opportunities (growing population, technological changes, VAT reduction, etc.) which influence the factory development in the external market, Furthermore, it determines strengths as (Credit facilities, have a good relation with the customers, a variety of furniture, accessible prices, etc. ) and weaknesses (limit personal experience, poor customer advice, lack of promotions) which are serving to see the strong and weak points. The methodology of this project was a descriptive investigation, quantitative approach, using techniques such as; Surveys, interviews and direct observation gather information of real and potential customers, which was essential with a substitutional diagnostic to develop the strategies….